Une analyse quantitative de la doctrine en droit civil québécois - Normand, Sylvio (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
Scholarly writings may be considered as one of the sources of the law of Québec. A minor source compared, for instance, to the decisions of the courts, but nevertheless a source. The following paper is an unpretentious attempt to quantify rather than qualify Québec legal writers' contributions to such source as regards civil law only. It takes into account treatises, monographies including unpublished thesis, and articles.